Multinational Companies:A Study of their Impact on India - Sambrani, Smitha (Indian Journal of Marketing, 2009)
Although the multinational corporation took birth in the early 1860’s, it was after the Second World War that the multinational has grown rapidly. In the early days, the United States was the home of majority of the MNC’s. Now there are a large number of Japanese MNCs and European MNCs are the largest in number. Multinationals have been emerging from the developing countries too. South Korea has, for example, well known MNC’s like Samsung, Hyundai and Daewoo. The growth of MNC’s has been the result of foreign direct investment. The global liberalization has paved the way for the fast expansion and growth of the MNCs. Multinational corporations have various factors or reasons responsible for the growth.